MiRNA160 is associated with local defense and systemic acquired resistance against Phytophthora infestans infection in potato - Natarajan, Bhavani; Kalsi, Harpreet S.; Godbole, Prajakta; Malankar, Nilam; Thiagarayaselvam, Aarthy; Siddappa, Sundaresha; Thulasiram, Hirekodathakallu V.; Chakrabarti, Swarup K.; Banerjee, Anjan K. (Journal of Experimental Botany, 2018)
To combat pathogen infection, plants employ local defenses in infected sites and elicit systemic acquired resistance (SAR) in distant tissues. MicroRNAs have been shown to play a significant role in local defense, but their association with SAR is unknown. In addition, no such studies of the interaction between potato and Phytophthora infestans have been reported. We investigated the role of miR160 in local and SAR responses to P. infestans infection in potato. Expression analysis revealed induced levels of miR160 in both local and systemic leaves of infected wild-type plants. miR160 overexpression and knockdown plants exhibited increased susceptibility to infection, suggesting that miR160 levels equivalent to those of wild-type plants may be necessary for mounting local defense responses. Additionally, miR160 knockdown lines failed to elicit SAR, and grafting assays indicated that miR160 is required in both local and systemic leaves to trigger SAR. Consistently, SAR-associated signals and genes were dysregulated in miR160 knockdown lines. Furthermore, analysis of the expression of defense and auxin pathway genes and direct regulation of StGH3.6, a mediator of salicylic acid-auxin cross-talk, by the miR160 target StARF10 revealed the involvement of miR160 in antagonistic cross-talk between salicylic acid-mediated defense and auxin-mediated growth pathways. Overall, our study demonstrates that miR160 plays a crucial role in local defense and SAR responses during the interaction between potato and P. infestans.
Keywords: Auxin-salicylic acid antagonism; microRNA; miR160; Phytophthora infestans; Solanum chacoense; Solanum tuberosum; systemic acquired resistance

Phased short-interfering RNA siRD29(-) regulates GIBBERELLIN 3-OXIDASE 3 during stolon-to-tuber transitions in potato - Malankar, Nilam; Kondhare, Kirtikumar; Saha, Kishan; Mantri, Mohit; Banerjee, Anjan (Plant Physiology, 2023)
Phased short-interfering RNAs (phasiRNAs) fine tune various stages of growth, development, and stress responses in plants. Potato (Solanum tuberosum) tuberization is a complex process, wherein a belowground modified stem (stolon) passes through developmental stages like swollen stolon and minituber before it matures to a potato. Previously, we identified several phasiRNA-producing loci (PHAS) from stolon-to-tuber transition stages. However, whether phasiRNAs mediate tuber development remains unknown. Here, we show that a gene encoding NB-ARC DOMAIN-CONTAINING DISEASE RESISTANCE PROTEIN (StRGA4; a PHAS locus) is targeted by Stu-microRNA482c to generate phasiRNAs. Interestingly, we observed that one of the phasiRNAs, referred as short-interfering RNA D29(-), i.e. siRD29(-), targets the gibberellin (GA) biosynthesis gene GIBBERELLIN 3-OXIDASE 3 (StGA3ox3). Since regulation of bioactive GA levels in stolons controls tuber development, we hypothesized that a gene regulatory module, Stu-miR482c-StRGA4-siRD29(-)-StGA3ox3, could govern tuber development. Through transient expression assays and small RNA sequencing, generation of siRD29(-) and its phase was confirmed in planta. Notably, the expression of StGA3ox3 was higher in swollen stolon compared to stolon, whereas siRD29(-) showed a negative association with StGA3ox3 expression. Antisense (AS) lines of StGA3ox3 produced more tubers compared to wild type. As expected, StRGA4 overexpression (OE) lines had high levels of siRD29(-) and mimicked the phenotypes of StGA3ox3-AS lines, indicating the functionality of this module in potato. In vitro tuberization assays (with or without a GA inhibitor) using StGA3ox3 antisense lines and overexpression lines of StGA3ox3 or StRGA4 revealed that StGA3ox3 controls the tuber stalk development. Taken together, our findings suggest that a phasiRNA, siRD29(-), mediates the regulation of StGA3ox3 during stolon-to-tuber transitions in potato. A phasiRNA module, Stu-miR482c-StRGA4-siRD29(-), regulates the expression of a gibberellin biosynthesis gene StGA3ox3 during stolon-to-tuber transitions in potato.